Currency Board Arrangements : Issues and Experiences - Enoch, Charles (Occasional Papers; Occasional Paper, 1997)
This paper provides a comprehensive analysis of the attractions and disadvantages of currency board arrangements in their various institutional configurations. It asks what defines a currency board arrangement, what are their strengths and weaknesses, and what constraints they place on macroeconomic policies. It also reviews country experiences with these arrangements.